PENGANGKATAN ANAK ANGKAT MENURUT HUKUM - Hasan Syazali; T. Sabirin (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2022)
This study aims to determine the practice of adopting children as well as review Islamic law and positive law regarding child adoption in society. This study uses the method of "library research" and "field research" document review, observation, and interviews. The results showed that the mechanism for implementing child adoption among the community, the stages carried out by the community there was no special event or other rituals in the adoption process, but only by doing small feasts, and the reason for adopting children was because families who adopted children tended to because they do not have children of their own. Then it is recommended to every adoptive parent to find out how the procedure for adopting a child is correct according to religion and state laws and regulations, and to religious leaders and community leaders so that they can socialize the procedures for adopting children by Islamic teachings and applicable regulations. regarding the adoption of children, so as not to cause problems in the future.